ответы в решениях
Пошаговое объяснение:
1) (x-2)/6+x/2=(5x-2)/9; (НОК (2,6,9) = 18);
3(x-2)+9x = 2(5x-2);
3x-6 + 9x = 10x - 4;
3x +9x - 10x = 6 - 4;
2x = 2;
x=1;
***
2) (5+2x)/3 = (x-3)/5 + (x+5)/2; (НОК (3,5,2)=30);
10(5+2х)= 6(x-3) + 15(x+5);
50+20x=6x-18+15x+75;
20x-6x-15x=75 - 18 - 50;
-x = 7;
x= -7.
***
3) 3(x+1)/8 + 2(5-x)/3 = (16-13x)/12; (НОК(8,3,12)=24);
9(x+1) + 16(5-x) = 32 - 26x;
9x+9 + 80-16x = 32-26x;
9x-16x+26x = 32 -9 -80;
19x = -57;
x= -3.
***
4) 5(7-2x)/3 - (4x-2)/9 = (x-19)/2; (НОК (3,9,2)=18);
30(7-2x) - 8x+4 = 9x-171;
210 - 60x - 8x + 4 = 9x-171;
-60x - 8x -9x = -171 -210 - 4;
- 77x = - 385;
x= 5.
|x - 4| * (2x + 7) = 0
Приравняем к нулю оба множителя:
|x - 4| = 0
2x + 7 = 0
Решим каждый:
|x - 4| = 0
x - 4 = 0
x = 4
2x + 7 = 0
2x = -7
x = - 7 : 2
x = -3.5
ответ: -3,5; 4
|x + 1,7| * (2x + 3) = 0
Приравняем к нулю оба множителя:
|x + 1,7| = 0
2x + 3 = 0
Решим каждый:
|x + 1,7| = 0
x + 1.7 = 0
x = -1.7
2x + 3 = 0
2x = -3
x = -3 : 2
x = -1,5
ответ: -1,5; -1,7
|5x - 8| * (x - 6) = 0
Приравняем к нулю оба множителя:
|5x - 8| = 0
x - 6 = 0
Решим каждый:
|5x - 8| = 0
5x - 8 = 0
5x = 8
x = 8 : 5
x = 1.6
x - 6 = 0
x = 6
ответ: 1,6; 6